2007
DOI: 10.1097/01.bot.0000250741.65003.14
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Thromboprophylaxis With Dalteparin After Surgical Treatment of Achilles Tendon Rupture: A Randomized, Placebo-Controlled Study

Abstract: DVT is common after surgical treatment of Achilles tendon rupture, and therefore effective thromboprophylaxis is desirable. In our study, thromboprophylaxis with dalteparin, however, does not affect the incidence of DVT during immobilization after Achilles tendon rupture surgery. Long-term effects of immobilization, such as the risk for postthrombotic syndrome, need to be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
152
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(160 citation statements)
references
References 20 publications
6
152
0
2
Order By: Relevance
“…Although there is general consensus regarding the use of prophylactic antithrombotic therapy after hip and knee surgery [4], there is no agreement regarding prophylactic therapy after Achilles tendon rupture. Lapidus et al [16] performed a randomized, placebo-controlled study of 91 patients with surgically treated Achilles tendon ruptures and found no beneficial effect of thromboprophylaxis with dalteparin in preventing DVT. The use of anticoagulation medications is not without side effects.…”
Section: Introductionmentioning
confidence: 97%
“…Although there is general consensus regarding the use of prophylactic antithrombotic therapy after hip and knee surgery [4], there is no agreement regarding prophylactic therapy after Achilles tendon rupture. Lapidus et al [16] performed a randomized, placebo-controlled study of 91 patients with surgically treated Achilles tendon ruptures and found no beneficial effect of thromboprophylaxis with dalteparin in preventing DVT. The use of anticoagulation medications is not without side effects.…”
Section: Introductionmentioning
confidence: 97%
“…[35] Lapidus et al, [36] however, found a 28% DVT rate in patients after ankle fracture surgery who did not receive pharmacological prophylaxis. In two studies following Achilles tendon rupture repair, the incidences of DVT were 36% [19] and 6%. [26] In a more recent prospective study, we found an 8.5% incidence of VTE in patients who required immobilisation in a below-knee cast and non-weightbearing for ≥4 weeks after foot and ankle surgery.…”
Section: Researchmentioning
confidence: 99%
“…[6,[8][9][10][11][12][13][14][15][16][17][18][19][20]26,37,41] A difficulty of long-term follow-up of patients is that many DVT events occur several weeks or longer after discharge. [37,42] …”
Section: Researchmentioning
confidence: 99%
“…Five trials met our search criteria [4,[12][13][14][15]. All five trials compared thromboprophylaxis by low molecular weight heparin to no prophylaxis or placebo.…”
Section: Resultsmentioning
confidence: 99%